Carcass and Meat Characteristics of Male Bali Cattle in Indonesian Smallholder Farms Fed Ration with Different Protein Levels - Tahuk, P. K.; Budhi, S. P. S.; Panjono, Panjono; Baliarti, E. (Tropical Animal Science Journal, 2018)
The objective of research was to determine the effect of different protein levels on the carcass and meat characteristics of male Bali cattle fattened in smallholder farms. The cattle used were 18 heads aged 2 to 2.5 years with initial body weight of 229.86±12.46 kg. The experimental cattle were randomly divided into 3 treatment groups i.e., T₀, T₁, and T₂. The T₀ group cattle were fed ration according to traditional practices of fattening cattle by farmers (100% forage). The T₁ group cattle were fed ration with 12% CP and 72% TDN. The T₂ group cattle were fed ration with 15% CP and 72% TDN. The variables measured were final body weight and the characteristics of the carcass (meat, fat, and ratio of meat to bone), and meat quality including the chemical composition of the meat (protein, fat, and collagen), meat tenderness, cooking loss, water holding capacity, and degree of acidity (pH). Data were analyzed by variance analysis. Results of research showed that the final body weight, and weight of carcass, meat, and fat of T₁ and T₂ groups were similar; conversely, those parameters in T₀ group cattle were lower (P